Modeling the interaction across international conventional and Islamic stock indices - Abdul Hakim; Awan Setya Dewanta; Sahabudin Sidiq; Riska Dwi Astuti (Cogent Economics & Finance, 2021)
Islamic financial instruments have been experiencing rapid growth in the last 50 years. Despite the unique motivation in formulating them, namely based on Syariah law, their movement might link to those of the conventional ones. This paper is devoted to investigating such interactions. It does so by applying two multivariate time series models to estimate various instruments, both Islamic and conventional ones. The models are the VAR (Vector Autoregression) and the VARMA-GARCH (Vector Autoregressive Moving Average-Generalized Autoregressive Heteroskedasticity). From the VAR model it finds evidence of bidirectional influences across both instruments. It also finds a conventional stock index that dominates the other series, namely the DJI (Dow Jones Index). From the VARMA-GARCH model, it finds influences from the conventional to Islamic index and vice versa, both in conditional mean and conditional variances. This paper suggests that the behavior of Islamic instruments are inseparable from the conventional ones. Future research might consider conditional correlations across these variables.
Keywords: F37; G15; 330; conventional instruments; interaction; Islamic instruments; Syariah law